Brazilian Portuguese Version of Intrinsic Motivation Inventory (IMI-Teq Br): Towards a Digital Well-Being Culture in Brazil - Nunes, Caio; Darin, Ticianne (Journal of the Brazilian Computer Society, 2024)
Self-determination theory (SDT), a foundational psychological framework, has emerged as a pivotal lens through which to understand the dynamics of human-computer interaction (HCI) and Games User Research (GUR). Central to SDT is the conceptualization of intrinsic motivation, characterized by voluntary behaviors arising fro personal interest. An established method for assessing intrinsic motivation across various contexts is the employment of the Intrinsic Motivation Inventory (IMI). This study presents a meticulous translation and cross-cultural adaptation of the 22-item version of IMI, known as the Task Evaluation Questionnaire, into Brazilian Portuguese (IMI Teq Br). The process adhered to the comprehensive methodology outlined by Beaton, encompassing Translation, Synthesis, Back-translation, Expert Committee review, and Pre-testing phases. Statistical analyses, including Student’s T-test for independent samples, Exploratory Factor Analysis (EFA), and Confirmatory Factor Analysis (CFA), were conducted to ensure the validity and reliability of the translated instrument. Our findings corroborate the robustness of the adapted questionnaire, affirming its suitability for use within the Brazilian Portuguese-speaking context. This paper meticulously delineates the adaptation process and resultant statistical outcomes, offering insights into the significance of IMI Teq Br for engagement and motivation research grounded in SDT principles. Additionally, we thorougly discuss the challenges inherent to this context in Brazil, providing valuable considerations for future endeavors.